The Effectiveness of Samapta Patrols in Preventing Motor Vehicle Theft Crimes in the Legal Area of ​​the Madiun City Police (Advances in Police Science Research Journal, 2024)
Patrol is a form of activity that moves from one place to another carried out by members of the National Police Samapta in order to prevent criminal acts from occurring, and provide a sense of security to the community. However, in its implementation the Samapta Patrol is still not effective in handling criminal acts of theft. This is proven by the increasing number of criminal acts of theft. A qualitative approach was used in this research to gain an understanding of "the effectiveness of Samapta patrols in preventing motor vehicle theft crimes in the Madiun City Police jurisdiction" both in implementation by the Madiun City Police Samapta Unit and efforts to make them effective. The type of research used is field research which is carried out by collecting information obtained from respondents through structured interviews. This research also uses theories and concepts that are in line with the research title, including Management Theory, Crime Prevention Concept, Patrol Concept, Effectiveness Concept and Theft Concept. The results of the research found that there were deficiencies in implementation management and management of organizational resources, such as not having the right target and time for carrying out patrol activities, lack of awareness of personnel in carrying out troop leadership and consolidation events, patrols carried out seemed to be just documentation, lack of personnel who were not in accordance with list of personnel composition (DSP) and vocational education (DIKJUR), as well as a lack of fuel oil (BBM) in carrying out patrols. However, behind these shortcomings there are things that support the implementation of patrols to continue to be carried out, such as adequate facilities and infrastructure, budget which is distributed well to members, and in this case the Madiun City Police Satsamapta applies the dialogical patrol method in carrying out active operations.
Keywords: efektivitas; patroli; tindak pidana